THE ACHIEVEMENT OF SUSTAINABILITY DEVELOPMENT GOALS (SDG’S) IN COMMUNITY EMPOWERMENT WITH PARTICIPATORY RURAL APPRAISAL APPROACH (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This research is a research on empowerment of human resources in regional government apparatus in achieving the goals stated in the SDGs. Sustainability Development Goals (SDGs) has been implemented using 17 indicators. All of the countries that are members of the MDGs declaration have participated in the SDGs declaration, including Indonesia. In general, this research aimed to further analyze the implementation of SDGs implementation with the implementation of human resource empowerment through the application of Participatory Rural Appraisals (PRA). In particular, this research provided input to regional governments in the achievement of SDGs’ goals implementation for harmonizing government regulations and programs with community empowerment.This research was conducted by reviewing the case studies about achievement of SDGs’ goals in Batu City. This research was conducted by observing the regional organizations (OPD) related to poverty reduction policies and the readiness of regional governments in implementing SDGs. This research was done by conducting interview, distributing questionnaire and FGD with regional government officials in the OPD that carried out programs related to achievement of SDGs. The analysis was carried out with descriptive qualitative by combining statistical analysis to strengthen the results of descriptive analysis, namely by using frequency analysis to determine respondents' responses to the questionnaire. The results of this research indicated that some of the objectives listed in the SDG document have been successful, however, they were still not optimal, especially in terms of sustainable economic development. This finding encouraged the regional government to be more extra in terms of achieving economic equality so that it would also have effect on lower class society.